2018
DOI: 10.1136/jim-2017-000638
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Chronic Comorbidities and the Atherosclerosis Indicators Ankle-Brachial Index and Brachial-Ankle Pulse Wave Velocity in Patients with Type 2 Diabetes Mellitus

Abstract: This study aimed to determine associations between ankle-brachial index (ABI) and brachial-ankle pulse wave velocity (baPWV) with different comorbidities in patients with type 2 diabetes mellitus (DM). Records of patients with type 2 DM who received an ABI and baPWV examination between August 2013 and February 2015 were retrospectively reviewed. Associations of ABI and baPWV with chronic kidney disease (CKD), chronic liver disease (CLD), coronary artery disease (CAD) and diabetic nephropathy (DN) were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
5
0
2
Order By: Relevance
“…To the best of our knowledge, this is the first study that evaluated the association between DKD and ABI in Caucasian patients with T2DM. A study in Japanese patients showed no correlation between ABI and eGFR [ 39 ], whereas a report from Taiwan revealed an independent association between ABI and DKD [ 40 ]. Given these limited data, particularly in non-Asians, and that ABI is an inexpensive, non-invasive, easily performed and sensitive marker of cardiovascular risk [ 10 , 14 ], more studies are needed to characterize the usefulness of ABI as a risk stratification tool in patients with DKD.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study that evaluated the association between DKD and ABI in Caucasian patients with T2DM. A study in Japanese patients showed no correlation between ABI and eGFR [ 39 ], whereas a report from Taiwan revealed an independent association between ABI and DKD [ 40 ]. Given these limited data, particularly in non-Asians, and that ABI is an inexpensive, non-invasive, easily performed and sensitive marker of cardiovascular risk [ 10 , 14 ], more studies are needed to characterize the usefulness of ABI as a risk stratification tool in patients with DKD.…”
Section: Discussionmentioning
confidence: 99%
“…As PWV is a measure of the time it takes the pulse to travel between the 2 arterial points, it is a direct measure of arterial stiffness. PWV is proportional to the speed of pulse wave through the arterial walls: when the blood vessels are young and elastic, the speed of the pulse wave traveling along the arterial wall is low; otherwise, in stiffened artery, the PWV is high [ 22 ]. Although carotid-femoral pulse wave velocity(cfPWV) is considered a gold standard non-invasive measure of arteria stiffness and has abundant clinical data [ 16 , 32 ], it has several shortcomings such as technical difficulty and inconvenience to the patients during the exam [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our study group reported significant correlations between baPWV and several cardiovascular risk scores including 2013 ACC/AHA ASCVD risk score [ 22 ]. The aim of this study is to compare prognostic value between baPWV and 2013 ACC/AHA ASCVD risk score, and to determine whether baPWV has incremental value to 2013 ACC/AHA ASCVD risk score in predicting future cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan riwayat komorbid pada penelitian ini sebagian besar responden tidak memiliki riwayat penyakit komorbid yaitu sebanyak 37 orang (61,7%). Studi yang dilakukan oleh Lee et al (2018) menunjukkan bahwa ABI merupakan data penunjang utama untuk diagnosis PAP memiliki asosiasi dengan insiden penyakit kronis meliputi diabetes mellitus, penyakit kardiovaskular (hipertensi, hiperkolesterolemia, dan merokok). Hasil analisis regresi pada studi Lee et al (2018) menunjukkan bahwa nilai rata-rata skor ABI pada pasien dengan komorbid mengalami penurunan dibandingkan nilai normal (10).…”
Section: Pembahasanunclassified